Conessine as A Novel Anti-Quorum Sensing Agent against Streptococcus mutans: An in vitro Analysis of Biofilm Inhibition - Alsaadi, Khloud H (Indian Journal of Pharmaceutical Education and Research)
Background: Dental caries concerns not solely the painful decay and eventual loss of the tooth but also significantly impacts an individual's physical, mental, and social health. The quest for potential Quorum Sensing (QS) inhibitors to hinder virulence, especially to mitigate the emergence of antibiotic resistance among caries pathogens, is increasing in this era of finding treatments from natural resources. Objectives: With the goal of finding a novel QS inhibitor, a plant alkaloid, conessine, has been evaluated for its inhibitory effect on biofilm formation, mature biofilm, and pathogen adherence against cariogenic Streptococcus mutans. Materials and Methods: The inhibitory effect of conessine on biofilm formation, as well as on developed biofilm was assessed using crystal violet assays. Colony-Forming Unit (CFU) counts on Mueller Hinton Agar were used to measure the inhibition of pathogen adhesion. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of conessine were determined using broth dilution assays. The live/dead cell analysis was performed using fluorescence microscopy, and quantitative Real-Time PCR (qRT-PCR) was employed to assess the expression of virulence genes StrepB and StrepgbpA. One-way ANOVA and Dunnett’s test were used to analyze the statistical significance (p<0.001). Results: At the lower concentration (6.25±0.4 μg/mL) used in this study, conessine significantly inhibited biofilm formation and matured biofilm, with the inhibition rates of 23 and 29%, respectively. Adhesion was inhibited entirely at 100 μg/mL concentration of conessine. Conessine demonstrated the growth inhibition of S. mutans, with MIC50 at 31.811±2.01 μg/ mL and MBC (IC90) at 70.1252±3.56 μg/mL. Images from fluorescence microscopy confirmed S. mutans cell death at conessine MIC50. Downregulation of StrepB and StrepgbpA genes, with the fold change 1.05 and 1.17, indicating the molecular mechanism behind reduced adherence and biofilm formation, respectively. Conclusion: This study is the first to demonstrate the potential anti-QS and anti-biofilm properties of conessine against S. mutans in vitro, suggesting it as a novel therapeutic agent for dental caries. Further investigations are needed to analyze the toxicity and optimize the anti-cariogenic properties at lower doses to assess clinical safety.
Keywords: Phytochemicals; Anti-Biofilm; Anti-caries; Virulence; Tooth Decay.